2012
DOI: 10.1074/mcp.m112.018853
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Punch Packed in Venoms Makes Centipedes Excellent Predators

Abstract: Centipedes are excellent predatory arthropods that inject venom to kill or immobilize their prey. Although centipedes have long been known to be venomous, their venoms remain largely unexplored. The chemical components responsible for centipede predation and the functional mechanisms are unknown. Twenty-six neurotoxin-like peptides belonging to ten groups were identified from the centipede venoms, Scolopendra subspinipes mutilans L. Koch by peptidomics combined with transcriptome analysis, revealing the divers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
148
1
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 113 publications
(153 citation statements)
references
References 38 publications
2
148
1
2
Order By: Relevance
“…In this study we examined centipede venom as a potential source of selective Na V 1.7 inhibitors because we previously demonstrated that these venoms are replete with ion channel modulators (14). We described the purification and functional characterization of a unique peptide (Ssm6a) with potent analgesic properties from venom of the centipede S. subspinipes mutilans.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In this study we examined centipede venom as a potential source of selective Na V 1.7 inhibitors because we previously demonstrated that these venoms are replete with ion channel modulators (14). We described the purification and functional characterization of a unique peptide (Ssm6a) with potent analgesic properties from venom of the centipede S. subspinipes mutilans.…”
Section: Discussionmentioning
confidence: 99%
“…S1) indicates that the six cysteine residues form three disulfide bonds. A BLAST search of the protein/DNA sequence databases revealed that Ssm6a is not similar to any known peptide or protein, except for ∼40% sequence identity with κ-SLPTX-Ssm1a that we recently isolated from the venom of the same centipede (14).…”
Section: Significancementioning
confidence: 99%
See 2 more Smart Citations
“…The venom peptides, which are of most interest from a drug discovery perspective, are extraordinarily diverse [25,[27][28][29][30][31][32]. Undheim et al [30] classified centipede venom peptides into 31 phylogenetically distinct families of scutigerotoxins (SCUTX1-3) and scoloptoxins ( .…”
Section: Centipede Venoms Are Complex Chemical Arsenalsmentioning
confidence: 99%